1957
DOI: 10.1161/01.res.5.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Collateral Blood Flow to the Dog's Lung

Abstract: The collateral circulation of the lung, i.e., that part of the bronchial flow which drains into the pulmonary veins, was studied by a heart-lung arrangement in which the lesser and systemic circuits of dogs could be perfused separately. In this preparation the collateral supply amounted to 0.5 to 1 per cent of the total arterial flow under approximately normal conditions. The changes in this collateral flow under a variety of experimental conditions were studied. These included variable systemic, venous and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1959
1959
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The major hemodynamic and neural determinants of bronchopulmonary flow have been studied by several groups over the past four decades. The majority of investigators (3)(4)(5)(6)(7)(8)(9) have found that systemic arterial pressure, independent of cardiac output, is one of the principal factors determining bronchopulmonary shunt flow. Although the exact anatomic location of the connections between the bronchial and pulmonary circulations is a subject of some controversy (10, 1 1), all agree that the pulmonary arterial and venous pressures, reflecting the "outflow pressure" ofthe bronchopulmonary anastomoses, are also principal determinants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major hemodynamic and neural determinants of bronchopulmonary flow have been studied by several groups over the past four decades. The majority of investigators (3)(4)(5)(6)(7)(8)(9) have found that systemic arterial pressure, independent of cardiac output, is one of the principal factors determining bronchopulmonary shunt flow. Although the exact anatomic location of the connections between the bronchial and pulmonary circulations is a subject of some controversy (10, 1 1), all agree that the pulmonary arterial and venous pressures, reflecting the "outflow pressure" ofthe bronchopulmonary anastomoses, are also principal determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact anatomic location of the connections between the bronchial and pulmonary circulations is a subject of some controversy (10, 1 1), all agree that the pulmonary arterial and venous pressures, reflecting the "outflow pressure" ofthe bronchopulmonary anastomoses, are also principal determinants. Systemic venous pressure, as a determinant of the outflow pressure of the bronchial veins, can modify the fraction of bronchial arterial blood that flows into the broncho-pulmonary anastomoses (5,6). Increasing intrapulmonary pressure and positive end-expiratory pressure can decrease bronchopulmonary flow independent of primary changes in intravascular pressures (7,9,(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The higher left ventricle output was always associated with collateral blood flows in the lungs, i.e., with the entry of blood from systemic into pulmonary vessels via anastomoses between these vessels. Extensive research of collateral circulation in the lungs [8][9][10][11][13][14][15][16]18,19] revealed the existence of intervessel communications of the following types. First, anastomoses between bronchial and pulmonary vessels at precapiltary, capillary, and postcapillary levels have been described in mammals of various species.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, the collateral blood flow in the lungs amounts to 0.3-3.5% of the left ventricle output, although individual variations can be considerable [8][9][10][11]18]. The possibility of augmenting collateral blood flow in cases of pulmonary artery occlusion (PAO) has been under discussion for a long time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation